18F‐FDG PET‐CT in a patient with methotrexate‐associated lymphoproliferative disorder. (2nd December 2017) - Shimizu, Hayato; Nishioka, Hiroaki
Abstract : 18 F‐FDG PET‐CT clearly demonstrated the disease activity of MTX‐LPD.